'That boy needs therapy': Constructions of psychotherapy in popular song lyrics. Issue 4 (2nd October 2017) - Hadjiosif, Miltiades; Coyle, Adrian
Abstract: Despite a plethora of academic and clinical descriptions of psychotherapy, less research attention has been focused on the ways in which psychotherapy is talked about and represented in popular culture. This study investigates constructions of psychotherapy in the lyrics of popular songs and identifies the vocabularies, versions and relevant discourses that are invoked or crafted. A critical discourse analysis was applied to 24 songs and yielded three broad themes: 'Banal therapy', the 'Non-therapeutic relationship' and 'I know therefore I can'. These discursive objects are examined in light of a constructionist understanding of knowledge and power within a discussion of how their interplay is implicated in the status of psychotherapeutic concepts and practices as 'expert knowledge'. Some clinical implications are attended to without making claims that this study has identified ontological representations of psychotherapy in popular culture.